Arthroscopically Assisted Treatment of Complex Ankle Fractures: Intraarticular Findings and 1-year Follow-up. Issue 3 (14th September 2018) - Polzer, Hans; Baumbach, Sebastian; Braunstein, Mareen
Category: Arthroscopy Introduction/Purpose: Especially after complex ankle fractures, patients suffer from residual pain, swelling and stiffness. Evidence suggests that this poor outcome might be related to occult intraarticular injuries. Recent studies documented chondral lesions in up to 89%. Therefore, many authors emphasize the value of ankle arthroscopy in acute fracture treatment (AORIF). Only few studies reported on the findings of AORIF, even less documented the subjective and objective outcome thereafter. Aim of this study was to evaluate the intraarticular lesions and the results following AORIF for complex ankle fractures after 1-year of follow-up. Methods: Patients presenting with closed, complex ankle fractures were included. AORIF was performed following a standardized protocol. Primary outcome was the AOFAS Score. Secondary outcome parameters were the Olerud and Molander Score, Tegner activity scale, arthroscopic findings, functional assessment and complications. Statistical analysis was performed using SSPS 22.0 (IBM). Results: Between 05/13-12/14, 32 patients were enrolled (56% female, 45±16 years). Three patients were lost to follow-up. 16% suffered from uni-, 22% from bi- and 62% from trimalleolar fractures. Chondral lesions were observed in 91% (ICRS 2.9±0.9). In 34% micro fracturing was performed. Full thickness lesions were observed exclusively in in bi- and trimalleolar fractures. Three patients suffered from minor complications. After 1 year, the mean AOFAS was 93±6 and the mean OMAS was 88±8. Linear regression revealed no significant variables affecting the outcome. Conclusion: Intra-articular injuries are common in complex ankle fractures requiring chondral therapy in 34%. AORIF leads to good-excellent results in all but one patient, including those with bi- and trimalleolar fractures without increasing the risk for complications.